2019
DOI: 10.1136/esmoopen-2019-000531
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CRP levels indicate poor progression-free and overall survival on cancer patients treated with PD-1 inhibitors

Abstract: BackgroundAnti-PD-(L)1 agents are standard of care treatments in various cancers but predictive factors for therapy selection are limited. We hypothesised that markers of systemic inflammation would predict adverse outcomes in multiple cancers treated with anti-PD-(L)1 agents.Material and methodsDiscovery cohort consisted of patients who were treated with anti-programmed cell death protein-1 (PD-1) agents for advanced melanoma (MEL), non-small cell lung cancer (NSCLC) or renal and bladder cancers (GU) at Oulu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 45 publications
6
59
0
Order By: Relevance
“…We found that elevated pretreatment CRP levels were associated with poor disease outcome as indicated with shortened PFS and OS. This is in line with previous studies investigating the prognostic impact of pretreatment CRP levels in cancer patients treated with ICI [ 27 , 28 , 29 , 36 , 37 ]. Suzuki et al showed a strong association between elevated pretreatment CRP levels and worse OS in patients with metastatic renal cell carcinoma treated with nivolumab.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that elevated pretreatment CRP levels were associated with poor disease outcome as indicated with shortened PFS and OS. This is in line with previous studies investigating the prognostic impact of pretreatment CRP levels in cancer patients treated with ICI [ 27 , 28 , 29 , 36 , 37 ]. Suzuki et al showed a strong association between elevated pretreatment CRP levels and worse OS in patients with metastatic renal cell carcinoma treated with nivolumab.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, recent studies have indicated that pretreatment CRP may represent a valuable prognostic marker in the immunotherapy setting of advanced NSCLC [ 27 , 28 , 29 ]. However, these studies were either limited by a very small sample size or the lack of an external validation.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand the mechanisms behind treatment responses to expand the proportion of patients benefiting from these treatments. A high NLR has been reported to be a marker of poor prognosis also in cancer patients treated with PD-1/PD-L1 inhibitors [24]. Thus, trastuzumab's possible ability to modulate the blood lymphocyte and neutrophil counts provides a rationale for combining trastuzumab with IO-treatments.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports, including our report, that ICI treatment has less efficacy in patients with poor PS or high CRP. It is thought that these are due to immunosuppression and the relationship with inflammatory cytokines [31][32][33], but the reasons are not clear. Therefore, CRP is not a clear biomarker.…”
Section: Discussionmentioning
confidence: 99%